The association between plant-based diet indices and metabolic syndrome: a systematic review and dose–response meta-analysis - Nikparast, Ali; Etesami, Elahe; Rahmani, Jamal; Rafiei, Nazgoli; Ghanavati, Matin (Frontiers in Nutrition, 2024)
Aim/Introduction: The prevalence of metabolic syndrome (MetS) and its components have markedly increased worldwide. Among lifestyle factors introduced to lower the risk of MetS, healthy dietary patterns have gained considerable attention. This study aimed to assess the association between adherence to plant-based diet indices including O-PDI (overall plant-based diet index), H-PDI (healthy plant-based diet index), U-PDI (unhealthy plant-based diet index), and risk of MetS development. Methods: To find related observational studies which assessed the association between Plant-based Diet indices and risk of MetS development, PubMed/Medline, Scopus, and Web of Science databases were searched from January 2016 to November 2023. A random effects model was used to estimate pooled odds ratios (OR) and 95% confidence intervals (95% CI). To assess the heterogeneity of included studies, the I2 index was used. Results: Nine studies including 34953 participants from the initial 288 studies were recognized to include in this meta-analysis study. According to pooled analysis, there was a significant relationship between the adherence to H-PDI and the lower risk of MetS (ES: 0.81; 95% CI: 0.67, 0.97; I²= 77.2%, p<0.001), while greater adherence to U-PDI was associated with 27% increases in the risk of MetS (ES: 1.27; 95% CI: 1.05, 1.54; I²= 76.8%, p<0.001). According to our analysis of the association between adherence to PDIs and the risk of MetS components, greater adherence to O-PDI and H-PDI was significantly associated with a higher risk of elevated FBS and obesity, respectively. As well, greater adherence to U-PDI was significantly associated with a higher risk of obesity, hypertriglyceridemia, low HDL-C, and elevated FBS. Conclusion: Our results highlighted the importance of food choices in the context of a plant-based dietary pattern, indicating that adherence to unhealthy plant-based dietary patterns rich in less healthful carbohydrates may induce the risk of MetS development.